2020
DOI: 10.1149/1945-7111/abcd11
|View full text |Cite
|
Sign up to set email alerts
|

Review—Knowledge-Based Process Design for High Quality Production of NCM811 Cathodes

Abstract: Low-cost and high-performance lithium ion batteries (LIBs) are a key technology in these days. One promising candidate for cathodes is the layered nickel (Ni)-rich LiNi0.8Co0.1Mn0.1O2 (NCM811) active material due to its high energy density, high specific capacity and lower material costs as well as social aspects concerning mining due to the diminished cobalt content. However, the lower thermal stability and higher sensitivity to H2O and CO2 result in a potential stronger performance degradation and lower safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 104 publications
0
44
0
Order By: Relevance
“…Cell safety is affected by increased internal cell pressure, caused by to the formation of gaseous hydrogen fluoride, as high internal cell pressure can lead to cell bursting. In addition, the acidic hydrogen fluoride can promote decomposition and corrosion of the active materials [12–14] . The compounds resulting from high residual moisture contents can impede the formation of a stable solid electrolyte interface (SEI), which protects the anode against the electrolyte, or affect an already existing SEI.…”
Section: Introductionmentioning
confidence: 99%
“…Cell safety is affected by increased internal cell pressure, caused by to the formation of gaseous hydrogen fluoride, as high internal cell pressure can lead to cell bursting. In addition, the acidic hydrogen fluoride can promote decomposition and corrosion of the active materials [12–14] . The compounds resulting from high residual moisture contents can impede the formation of a stable solid electrolyte interface (SEI), which protects the anode against the electrolyte, or affect an already existing SEI.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that nickel-rich materials such as LiNi 0,8 Mn 0,1 Co 0,1 O 2 (NMC 811) are sensitive to moisture and environmental conditions. [38,[60][61][62] To be able to track the possible influence of the production environment on the quality of the produced electrodes, parameters such as the type of the production environment, including a clean room or dry room with a specific dew point, the temperature of the room, and atmospheric humidity and pressure should be taken into account. [63]…”
Section: Raw Materials and Production Environmentmentioning
confidence: 99%
“…4,5 As a determining factor for electrochemical performance of LIBs, the cathode side has attracted great research interest over the years. [6][7][8][9] So far, a large variety of promising high-energy cathode materials have been developed for LIBs, which could be roughly divided into three categories according to their crystal structures, including layered oxides (such as LiCoO 2 , 10,11 LiNi 0.8 Co 0.1 Mn 0.1 O 2 , 12,13 ), and olivine phosphates (such as LiFePO 4 22,23 ). However, the climbing of the energy density of cathode materials usually implies high capacity or high working voltage, which makes the cathode materials harmfully unstable, aggravating the capacity fading of LIBs.…”
Section: Introductionmentioning
confidence: 99%